A Map of eLearning Acceptance (MeLA) and a Corporate eLearning Readiness Index (CeLeRI) - Succi, Chiara; Cantoni, Lorenzo (International Journal of Advanced Corporate Learning (iJAC), 2008)
This research aims at describing the conditions of eLearning acceptance, understanding the role of context and communication factors and providing a set of parameters to be considered when an eLearning activity is planned and proposed to eLearners. A blend of qualitative and quantitative methods has been chosen to achieve the research goals and build an eLearning Readiness Index. A first list of key factors has been identified through a comprehensive analysis of the literature on the acceptance issue; theories and models are presented focusing on phases, components and variables of the acceptance process and highlighting the importance of contextual factors. A general framework of analysis for the implementation of eLearning activities in organisations is built and presented in the Map of eLearning Acceptance (MeLA). The second part of the research zooms on MeLA considering only organizational context variables that affect the preparation phase of the eLearning acceptance process. The list of variables obtained in the literature review has been refined, assessed and organized through nine case studies and two surveys in order to define a Corporate eLearning Readiness Index. The main research output is a step forward in the comprehension and solution of the problem of eLearning acceptance and dropout. In particular, the Map of eLearning Acceptance and the Corporate eLearning Readiness Index (CeLeRI) offer two original tools to be further researched by eLearning researchers and to enter the eLearning practitionersâ?? toolbox.